2020
DOI: 10.2147/amep.s269059
|View full text |Cite
|
Sign up to set email alerts
|

<p>Study Habits of Urology Residents in Saudi Arabia: Identifying Defects and Areas for Curricular Development – A Trainee-Based Survey</p>

Abstract: This study evaluated the study habits of Saudi urology residents throughout their residency training. It examines the study time and quality of study materials used by Saudi urology residents and identifies ways to maximize study benefits. Patients and Methods: An online questionnaire was distributed to 152 registered residents in regions throughout Saudi Arabia (response rate: 93.4%). The questionnaire addressed study habits throughout training, motivations for studying, preferred study resources, impressions… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 29 publications
(48 reference statements)
2
6
0
Order By: Relevance
“…15 Most residents felt that their residency training program did not effectively prepare them for the board examination by not providing protected study time, similar to findings reported in a study performed on urology residents in the KSA. 16 In the current study, residents also reported that they preferred to study independently rather than in a group; this finding corroborates the result of a previous Saudi study performed on urology residents 16 though is in contrast to an American study, which found a prevalent preference for group study in undergraduate medical students. 17 The findings of our study highlighted several factors that were perceived to potentially negatively impact the academic performance of physiatry residents in the KSA, including a lack of structured or protected study time, difficulty accessing research publications, unengaging journal club events, and inadequate examination preparation.…”
Section: Discussionsupporting
confidence: 89%
“…15 Most residents felt that their residency training program did not effectively prepare them for the board examination by not providing protected study time, similar to findings reported in a study performed on urology residents in the KSA. 16 In the current study, residents also reported that they preferred to study independently rather than in a group; this finding corroborates the result of a previous Saudi study performed on urology residents 16 though is in contrast to an American study, which found a prevalent preference for group study in undergraduate medical students. 17 The findings of our study highlighted several factors that were perceived to potentially negatively impact the academic performance of physiatry residents in the KSA, including a lack of structured or protected study time, difficulty accessing research publications, unengaging journal club events, and inadequate examination preparation.…”
Section: Discussionsupporting
confidence: 89%
“…After applying the inclusion and exclusion criteria, 24 out of 15,291 articles were included (see Figure 1). 26–49 The rigor and relevance of each article is reported in Supplemental Digital Appendix 2 (at http://links.lww.com/ACADMED/B420).…”
Section: Resultsmentioning
confidence: 99%
“…Stimulation of autonomous motivation also happened if the assessment was poised to directly build competence and was an embedded active learning assessment, with timely, external, and multiple sources of feedback. 28 , 31 , 33 , 40 , 41 , 44 , 47 , 49 Assessments that included setting individual 40 or shared goals, 41 stimulated learners to reflect, 33 were jointly constructed by learners and teachers, 45 had authenticity with clinical practice, 26 , 28 , 35 , 37 , 38 , 49 encouraged sharing or shared group learning and responsibility, 27 , 39 , 41 , 44 and held personal value for students also stimulated autonomous motivation. 27 , 31 , 45 Certain student characteristics also form the context for autonomous motivation stimulation, such as high baseline autonomous motivational (for learning) levels, 39 having the motivation for personal achievement or satisfaction, or having a love of learning and passion for the topic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Data from Italy 44 showed majority of Italian urology residents experienced slowdown in their learning process and they spend at least two hours per day (85.2%), while few have four or more hours (32.5%). Study habits of urology residents in Saudi Arabia have been studied, 45 the study conducted a year before the pandemic time showed 37.3% spent 2–5 hours weekly. Juniors read significantly more than seniors (P = 0.034).…”
Section: Challenges For Urology Residency Trainingmentioning
confidence: 99%